Influenza A virus infection and pathology in nasal and periocular tissues after ocular inoculation in ferrets. Issue 6 (November 2022) - Gary, Joy M.; Ritter, Jana M.; Sun, Xiangjie; Maines, Taronna R.; Belser, Jessica A.
Influenza A viruses (IAV) cause mammalian infections following several transmission routes. Considering the anatomic proximity and connection between the nasopharynx and periocular tissues, there is a need to understand the dynamics of virus spread between these sites following both respiratory and nonrespiratory viral transmission. We examined virus distribution and associated inflammation within nasal and periocular tissues during the acute phase of H1N1 IAV infection in ferrets following intranasal or ocular inoculation. Ocular and intranasal inoculations with IAV caused comparable viral antigen distribution and inflammation in the nasal passages, though infection kinetics and magnitude differed by inoculation route. Ocular inoculation was associated with inflammation in the conjunctiva and lacrimal glands. Although intranasal inoculation was also associated with periocular inflammation, the onset was delayed relative to ocular inoculation. This work underscores the importance of investigating extrapulmonary tissues following mammalian infection with respiratory pathogens, even after intranasal inoculation.